2012
DOI: 10.1111/j.1365-2249.2012.04581.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of natural killer (NK) and NK T cells in the loss of tolerance in murine primary biliary cirrhosis

Abstract: SummaryOne of the major obstacles in dissecting the mechanism of pathology in human primary biliary cirrhosis (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…Shimoda et al [41] demonstrated killing activity of human NK cells targeting autologous biliary epithelial cells isolated from PBC patients and accumulation of CD56 + NK cells in close proximity to destructed bile ducts in PBC livers. Furthermore, murine PBC models have shown that depletion of NK cells at early stages might abrogate disease initiation [42]. These findings might be reflected by our observations showing a specific regulation of peripheral and intrahepatic NK cells in autoimmune/biliary disease comprising several cases of PBC patients.…”
Section: Discussionsupporting
confidence: 71%
“…Shimoda et al [41] demonstrated killing activity of human NK cells targeting autologous biliary epithelial cells isolated from PBC patients and accumulation of CD56 + NK cells in close proximity to destructed bile ducts in PBC livers. Furthermore, murine PBC models have shown that depletion of NK cells at early stages might abrogate disease initiation [42]. These findings might be reflected by our observations showing a specific regulation of peripheral and intrahepatic NK cells in autoimmune/biliary disease comprising several cases of PBC patients.…”
Section: Discussionsupporting
confidence: 71%
“…Eosinophils may also constitute some proportion of inflammatory cells (9,26,27). Natural killer (NK) cells and NK T cells account for approximately 5% of the cellular infiltrate and play important roles in initiating the breakdown of tolerance (28). Interdigitating dendritic cells have been detected between biliary epithelial cells, often near breaks in the basement membrane and in the periductal granulomatous response (4,29,30).…”
Section: Immunopathological Characteristics Of Damaged Biliary Epithementioning
confidence: 99%
“…PBC is considered to have an autoimmune aetiology, because highly specific anti-mitochondrial antibodies are present in nearly 95% of patients. The abnormal immune response during PBC development leads to the activation and expansion of autoreactive T and B lymphocytes, followed by the production of numerous inflammatory mediators345. As a result, the liver is subjected to a cascade of destructive events, including oxidative stress.…”
mentioning
confidence: 99%